Heutagogy-Based Digital Extensive Reading: Enhancing Students’ Critical Reading Skills in EFL Islamic Higher Education - Fitriani, Aries; Rizkiyah, Faiqotur; Wulandari, Fitriya Dessi (Institut Agama Islam Negeri Kudus, 2026)
This study investigates the application of the heutagogical teaching model through Digital Extensive Reading (DER) in enhancing university students’ critical reading competencies in an English as a Foreign Language (EFL) context. It focuses on three key aspects: (1) the implementation of heutagogy-based DER, (2) heutagogy-based DER’s role in developing critical reading skills, and (3) the implications of this model. The participants consisted of 35 EFL Islamic university students. Using a qualitative structural analysis, data were gathered through document analysis, questionnaires, interviews, field notes, and literature review. The findings reveal that heutagogy-based DER empowers students to select texts, set goals, and engage in reflective learning, thereby fostering learner autonomy and personalization. Through exposure to diverse digital platforms, peer discussions, and presentations, students enhanced their critical thinking by developing analytical skills and intercultural awareness. Moreover, this approach redefined teachers’ roles as facilitators, emphasized formative over summative assessment, and encouraged deeper, more meaningful engagement with reading.